ANALISIS PENGARUH KINERJA LINGKUNGAN DAN BIAYA LINGKUNGAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BEI - Usemahu, Rasni Hanipa (Journal of Applied Accounting, 2023)
The aim of this research is to examine the influence of environmental performance and environmental costs on the financial performance of state-owned companies listed on the Indonesia Stock ExchangeThe type of data used is index data in annual reports obtained from company annual reports in the form of. Market data in the form of stock prices, company returns and market returns were obtained from the Indonesia Stock Exchange website (www,jdx.co.id) and the OK Stock website (www,sahamok.com/emiten). The population in this research are publicly traded state-owned companies listed on the Indonesian Stock Exchange (BEI) in 2017-2021. The analytical method used is hypothesis testingBased on the results of the research conducted, it can be concluded that environmental performance in state-owned companies is still not implemented well, as evidenced by the sample selection process in this research which shows the lack of companies, both state-owned and private, that report their environmental performance reports regularly. Apart from that, environmental performance influences financial performance. This proves that environmental performance is able to influence the financial performance of a company and environmental costs have a positive and significant effect on financial performance. This proves that the more environmental costs incurred, the more a company's financial performance will increase.Keywords: environmental performance, environmental costs, financial performance.